Does a knee joint position sense test make functional sense? Comparison to an obstacle clearance test following anterior cruciate ligament injury. (May 2022) - Grinberg, Adam; Strong, Andrew; Häger, Charlotte K.
Abstract: Objectives: To evaluate knee joint position sense (JPS) among individuals with anterior cruciate ligament reconstruction (ACLR), cleared for return to sport, and investigate whether JPS errors are associated with outcomes of a functional obstacle clearance test (OC; downward vision occluded). Design: Cross-sectional. Setting: Controlled laboratory. Participants: Thirty-four individuals following ACLR, 23 non-athletic asymptomatic controls (CTRL), 18 athletes (ATH). Main outcome measures: absolute error (AE) and variable error (VE) for weight-bearing knee JPS (target angles: 40°, 65°); minimal distances of the lower extremity from the obstacle (at any time and vertical clearance; two obstacle heights). Results: Larger AE ( P = 0.023) and VE ( P = 0.010) were observed for CTRL compared with ACLR. CTRL also had larger OC distances for the trailing leg compared with ATH ( P ≤ 0.046) and greater variability compared to both other groups ( P ≤ 0.033). Moderate positive correlations ( R s ≥ 0.408, P ≤ 0.029) were observed between AE for the 40° angle and low-obstacle distances, for the injured ACLR leg. Conclusions: Knee JPS was worse in less-active individuals rather than following ACLR. Functional assessments like our OC test should complement isolated JPS tests, as they emphasize whole-body coordination and thus constitute more relevant estimations of proprioception. Highlights: Knee JPS was deficient in non-athletes rather than following ACLR rehabilitation. JPS errors positively correlated with obstacle clearance distances for the ACLR leg. Tests such as our OC task may add functional relevance to single-joint JPS assessments. Further development of functional proprioception tests is encouraged.